Dramatic Strategies Made Clear: The Feminist Politics in Griselda Gambaro's Puesta en claro - Sandra Cypess (Studies in 20th & 21st Century Literature, 1996)
In this essay I explore the feminist aspects of Puesta en claro, written in 1974, when Griselda Gambaro was not yet considered a writer who paid attention to feminine issues. Yet to the extent that Gambaro always focuses on the constellation of problems relating to power relations, she is including feminine and feminist issues in her text, and continues a tradition many critics relate to Sor Juana Inés de la Cruz, as I shall argue in my conclusion. Seen within the trajectory of Gambaro's dramaturgy, Puesta en claro, as a play from the 1970s is also remarkable in showing a change in the typical pattern of victimization for her characters. Her audience sees that it is possible for the victims to renounce their passivity and rebel. Moreover, she embodies that message in the sign of a blind, apparently defenseless, domesticated, dominated woman. I suggest that in the creation of the blind woman Gambaro comments on the significance of the male gaze, not as an inherent attribute, but as a controlling agent derived from the patriarchal system. She also shows that the private spaces of the domestic sphere to which women are relegated within the patriarchy can be reconstituted as a site of power.
Keywords: Griselda Gambaro; Puesta en claro; feminism; feminine issues; power; power relations; Sor Juana Inés de la Cruz; play; theatre; patriarchy; Argentine literature; Argentine theatre